Analysis of the novel “No se lo digas a nadie” as an instrument to understand masculinity and gender violence - Mormontoy-Morales, Adelguisa E. (2020)
Gender violence and violence against women in the public or private space is an expression of the domination that a human being, self-considered as hegemonic, and socio-culturally supported can exercise against the subordinated. Such hegemonic position is structurally sustained by socio-cultural characteristics or attributes “naturally” assigned to the masculine, and artificially considered as a fixed or unmodifiable position which is, rather, alternating or even overlapping. As a universal sequelae and, on the basis of the actual reality and of reports and pronouncements from national and international organizations, a significant set of quantitative and qualitative evidence of violence against women, with devastating direct or indirect consequences in the mental and physical health of women and of the people around them, particularly their children, can be documented; the final result constitutes a serious public health problem. The objective of this essay was to formulate an analysis of violence against women and gender violence through the study of masculinity and the construction of the hegemonic in the identity of men, using as an instrument Jaime Bayly’s novel No se lo digas a nadie.